Functional Popliteal Artery Entrapment Syndrome: Poorly Understood and Frequently Missed? A Review of Clinical Features, Appropriate Investigations, and Treatment Options. (7th September 2014) - Hislop, Matthew; Kennedy, Dominic; Cramp, Brendan; Dhupelia, Sanjay
Abstract : Functional popliteal artery entrapment syndrome (PAES) is an important and possibly underrecognized cause of exertional leg pain (ELP). As it is poorly understood, it is at risk of misdiagnosis and mismanagement. The features indicative of PAES are outlined, as it can share features with other causes of ELP. Investigating functional PAES is also fraught with potential problems and if it is performed incorrectly, it can result in false negative and false positive findings. A review of the current vascular investigations is provided, highlighting some of the limitations standard tests have in determining functional PAES. Once a clinical suspicion for PAES is satisfied, it is necessary to further distinguish the subcategories of anatomical and functional entrapment and the group of asymptomatic occluders. When definitive entrapment is confirmed, it is important to identify the level of entrapment so that precise intervention can be performed. Treatment strategies for functional PAES are discussed, including the possibility of a new, less invasive intervention of guided Botulinum toxin injection at the level of entrapment as an alternative to vascular surgery.